Form finding & structural optimization: A project-based course for graduate students in civil and architectural engineering - Coelho, Rajan Filomeno; Tysmans, Tine; Verwimp, Evy (Structural and multidisciplinary optimization, 2014)
Nowadays, accreditation organizations for engineering programs put more and more emphasis on learning outcomes integrating multifaceted competences (scientific and technical skills, but also teamwork, communication, etc.). In this context, this paper discusses the relevance of project-based learning initiatives for teaching structural optimization, in the light of recent literature on the subject, as well as based on our experience in a course on form finding and structural optimization at the Brussels Faculty of Engineering. Although each project-based course has its specificities related to the teachers, their expertise, and the curriculum philosophy, some general guidelines are proposed, stressing the importance of a proper understanding of the mathematical and physical concepts, but also underlining the need to ensure sufficient room for creativity among the students.